Effect of UMMB Supplementation on Metabolic and Oxidative Parameters in Rambouillet Cross Sheep during Peripartum Period - Singh, A P; Singh, R; Bhat, A M; Tikoo, A; Pathak, A K (Indian Journal of Animal Nutrition, 2019)
The study was conducted to assess the effect of supplementing urea molasses multi-nutrient blocks on body weight gain, hemato-biochemical parameters, mineral status and oxidative stress in crossbred Rambouillet sheep in advanced pregnancy. The animals were categorized into 2 group’s viz. group-A (control) and group-B (UMMB supplemented @ 50gm/day) with 6 animals in each group. Along with body weight, blood samples were collected at 4 weeks and 1 week before lambing, followed by 1, 4 and 8 weeks after lambing. The average body weight increase of UMMB supplemented animals was 40% compared with 21% among control group animals. In treatment group, there was significant increase (P<0.05) in Hb level at +4 and +8 weeks post lambing. No significant change was observed in PCV values. Significant (P<0.05) improvement was observed in calcium, phosphorus, magnesium, iron and zinc levels, however non significant increase (P>0.05) was observed in copper level of supplemented group. The oxidative stress parameters in both treatment and control group showed significant changes in both groups. The study concluded that UMMB being good source of protein, energy and minerals improved metabolic and oxidative status of sheep during peripartum period.